2015
DOI: 10.1093/cercor/bhv298
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Stimulation Over the Dorsolateral Prefrontal Cortex Increases the Impact of Past Expenses on Decision-Making

Abstract: Goal-directed choices should be guided by the expected value of the available options. However, people are often influenced by past costs in their decisions, thus succumbing to a bias known as the "sunk-cost effect." Recent functional magnetic resonance imaging data show that the sunk-cost effect is associated with increased activity in dorsolateral prefrontal cortex (dlPFC) and altered crosstalk of the dlPFC with other prefrontal areas. Are these correlated neural processes causally involved in the sunk-cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Furthermore, social norms are thought to be represented in the LPFC, and this area plays a key role in rule-based control 39 40 . In line with this notion, a recent study showed that anodal transcranial direct current stimulation (tDCS) of dorsal LPFC increases the sunk cost effect 41 . Therefore, tight coupling between these two regions might bias decision-making under the influence of sunk costs.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, social norms are thought to be represented in the LPFC, and this area plays a key role in rule-based control 39 40 . In line with this notion, a recent study showed that anodal transcranial direct current stimulation (tDCS) of dorsal LPFC increases the sunk cost effect 41 . Therefore, tight coupling between these two regions might bias decision-making under the influence of sunk costs.…”
Section: Discussionmentioning
confidence: 86%
“…For example, human and nonhuman primate value choices are subject to various biases such as framing effects (De Martino et al, 2006), choice repetition biases (Padoa-Schioppa, 2013; Samuelson and Zeckhauser, 1988), sunk cost effects (Bogdanov et al, 2015), and previous payoff biases (Noorbaloochi et al, 2015; Rorie et al, 2010). These biases, which become more pronounced with difficult decisions (Fleming et al, 2010; Padoa-Schioppa, 2013), are also observed in human perceptual decision making (Nicolle et al, 2011; Fleming et al, 2010; Noorbaloochi et al, 2015; Mulder et al, 2012; St John-Saaltink et al, 2016Akaishi et al, 2014), with correlational evidence for a link between neural and choice variability (St John-Saaltink et al, 2016; Hesselmann et al, 2008; Wyart and Tallon-Baudry, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Anodal tDCS applied on the DLPFC facilitate working memory processes [11]. Findings show that anodal tDCS over the right DLPFC may prevent working memory impairment induced by acute stress [12]. Stimulation of the primary motor cortex (M1) and dorsolateral prefrontal cortex (DLPFC) reduces the perception of pain.…”
Section: Discussionmentioning
confidence: 99%